Inaplicabilidad del artículo 10 del código orgánico integral penal en centros autorizados por norma inferior - Erika Gabriela, Cárdenas Pesantez (2016)
The National Assembly requires professionals in law and directors of public affairs to legislate on behalf of Ecuadorians, otherwise you may have dozens of regulations governing rights, but if they are poorly made would jeopardize the legal security. Then it is just and necessary issue as OFFENSE TYPE imprisonment in facilities or places not legally authorized and their respective PUNISHMENT. The Public Service Act - LOSEP, and its General Regulation, constitute the legal instrument governing the actions of human talent of public sector entities, so to apply sanctions on public servants or for disciplinary action According to these legal bodies should establish the administrative proceedings, before a grade of the offense committed by these servers, by the Unit Human Resource Management - UHRM then inform the appointing authority, who have relevance to initiate the administrative proceedings or file, as considered in the report, the same to be reasoned findings of fact and law, which in many cases is not fulfilled, so the sanctioning body is in the same institution belongs to sumariado public servant. The Constitution of the Republic of Ecuador states that everyone has the right to be tried by an independent and impartial constitutional principle that administrative matters not met since the sanctioning body is the same institution sumariado public servant. Given the problems described above decided to develop this research paper entitled: INAPPLICABILITY OF ARTICLE 10 PENAL CODE IN 5 COMPREHENSIVE ORGANIC CENTRES FOR LOWER STANDARD. Where I carry out an analysis of the doctrinal and legal issues raised, achieving demonstrate the failure of the law.